2015
DOI: 10.1007/s12264-014-1522-4
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling nanotubes between rat primary astrocytes and C6 glioma cells alter proliferation potential of glioma cells

Abstract: The tunneling nanotube (TNT) is a newly discovered, long and thin tubular structure between cells. In this study, we established a co-culture system for rat primary astrocytes and C6 glioma cells and found that TNTs formed between them. Most of the TNTs initiated from astrocytes towards C6 glioma cells. The formation of TNTs depended on p53. In addition, hydrogen peroxide increased the number of TNTs in the co-culture system. Established TNTs reduced the proliferation of C6 glioma cells. Our data suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 42 publications
2
61
0
3
Order By: Relevance
“…As it is reported in literature that TnTs are not observed in some glioma cellular models (Van der Vos et al, 2016), we checked if U87-MG cells and NHA cells herein used were able to form TnTs in vitro. The results showed that both types of cells were able to communicate between them by TnTs, as already reported (Zhang and Zhang, 2015;Rostami et al, 2017;Reindl et al, 2019), and the percentage of cells forming TnTs was similar between U87-MG and NHA cells. As TnTs have been grouped into two main classes, very thin (≤0.7 µm, measuring a minimum of 100-200 nm) and thick (≥0.7 µm, up to 1 µm; Gerdes et al, 2007), we analyzed the heterogeneity of TnTs formed by U87-MG and NHA.…”
Section: Discussionsupporting
confidence: 86%
“…As it is reported in literature that TnTs are not observed in some glioma cellular models (Van der Vos et al, 2016), we checked if U87-MG cells and NHA cells herein used were able to form TnTs in vitro. The results showed that both types of cells were able to communicate between them by TnTs, as already reported (Zhang and Zhang, 2015;Rostami et al, 2017;Reindl et al, 2019), and the percentage of cells forming TnTs was similar between U87-MG and NHA cells. As TnTs have been grouped into two main classes, very thin (≤0.7 µm, measuring a minimum of 100-200 nm) and thick (≥0.7 µm, up to 1 µm; Gerdes et al, 2007), we analyzed the heterogeneity of TnTs formed by U87-MG and NHA.…”
Section: Discussionsupporting
confidence: 86%
“…To test the effect of Wnt7a on TNT formation, CAD cells were treated with increasing concentrations of Wnt7a for 4 h (Fig A). In these experiments, 200 μM of H 2 O 2 treatment was used as a positive control for TNT induction (Gousset et al , ; Zhang & Zhang, ). We found that Wnt7a is able to increase the percentage of TNT‐connected cells in a dose‐dependent manner (Fig A and B).…”
Section: Resultsmentioning
confidence: 99%
“…aid glioma cells in infiltrating the surrounding parenchyma. [154][155][156] The expression of connexin 43 (Cx43) 157 and different ATP-dependent ion channels (ClC-3, VGCC, TRPs, hERG, ENaC, CLICs) 158 in reactive astrocytes offer protection against radio-and chemotherapy via activation of Bcl2 family proteins and inhibition of cytochrome c release from mitochondria. 159 It is also reported that reactive astrocytes supply a suitable microenvironment for the transformation of CD133 + glioma stem cells from CD133 − cells.…”
Section: Role Of Neurovascular Unit In Ischemia and Glioma Astrocytesmentioning
confidence: 99%